PROMOTIONAL STRATEGIES AND TOURISM DESTINATION LOYALTY IN OSHOGBO, OSUN STATE - Ollor, Helen Y.; Olaleye, Abimbola Margaret (BW Academic Journal, 2022)
This study focused on Promotional Strategies and Tourism Destination Loyalty in Oshogbo in Osun State. The purpose of the study was to examine the relationship between Promotional Strategies using the dimensions of Promotional Strategies (Advertising, Public Relation) and the measures of Destination Loyalty (Repeat Visit and Referrals). The research adopted the Quasi Experimental Research Design. The study was conducted on the tourists in Osun Groove Destination in Oshogbo. The data collected for this work was from Primary Source (Questionnaire administration). Based on the Research Questions, Questionnaire of (100) copies were designed and (92) copies were retrieved. The sample population was determined by Taro Yamen sample size determination formula. These copies were analyzed and the Hypotheses were tested using Pearson Correlation Analytical Tool. The result revealed that there were no relationship between Promotional Strategies and Tourism Destination Loyalty. The study recommended that successful Tourism Marketing be based on information and what you know about your customers; how to reach them efficiently and effectively are very important. To understand whether your marketing activities are working, it would be essential to monitor and track the results of your efforts.